A STUDY ON THE RELATIONSHIP BETWEEN LABOUR WELFARE SCHEMES AND ITS IMPACT ON JOB SATISFACTION AMONG WORKERS IN TITAN WATCH COMPANY, HOSUR – A CASE STUDY - Mary, Viyani Jenita; S. Shanthi Getzie Ranjini Devi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In an industrial economy, the workers are subject to periodic unemployment due to cyclical fluctuations in business, sickness, industrial accidents and old age. In India it has the obligation from the Government side to help the labourers and provide them security and adopt labour welfare measures in the form of various schemes such as Workmen’s Compensation Act, Employees’ State Insurance Act, Finances and Contributions, Sickness benefit, Medical benefit, Maternity benefit, Disablement benefit, Dependents’ benefit, Employees’ Provident Fund and Bonus schemes, Gratuity Scheme and Employees’ Pension Scheme. All these welfare schemes have followed and adopted in industries for the welfare of labourers both men and women. So, the present study is done to understand the various labour welfare facilities such as statutory and non-statutory welfare facilities provided by the company to labourers / workers namely TITAN watch company, Hosur, and its impact on job satisfaction. This study shows the positive relation between welfare facilities such as medical facilities, crèche, canteen facilities, recreation, toilet facilities, rest room facilities, reading room, loan facilities for their children’s education, marriage, housing loan, insurance coverage etc. and job satisfaction. Job satisfaction is very important to know the level of contribution to workers towards his / her work and how welfare facilities affect. Labour welfare schemes are provided to strengthen man power in both physically and mentally. Thus, these facilities are more effective in improving the performance and building the morale of every worker working in industries, in order to increase the productivity of labourers.